Transnational inequities in cardiovascular diseases from 1990 to 2019: exploration based on the global burden of disease study 2019 - Hu, Ben; Feng, Jun; Wang, Yuhui; Hou, Linlin; Fan, Yinguang (Frontiers in Public Health, 2024)
Background To describe the burden and examine transnational inequities in overall cardiovascular disease (CVD) and ten specific CVDs across different levels of societal development. Methods Estimates of disability-adjusted life-years (DALYs) for each disease and their 95% uncertainty intervals (UI) were extracted from the Global Burden of Diseases (GBD). Inequalities in the distribution of CVD burdens were quantified using two standard metrics recommended absolute and relative inequalities by the World Health Organization (WHO), including the Slope Index of Inequality (SII) and the relative concentration Index. Results Between 1990 and 2019, for overall CVD, the Slope Index of Inequality changed from 3760.40 (95% CI: 3758.26 to 3756.53) in 1990 to 3400.38 (95% CI: 3398.64 to 3402.13) in 2019. For ischemic heart disease, it shifted from 2833.18 (95% CI: 2831.67 to 2834.69) in 1990 to 1560.28 (95% CI: 1559.07 to 1561.48) in 2019. Regarding hypertensive heart disease, the figures changed from-82.07 (95% CI: −82.56 to-81.59) in 1990 to 108.99 (95% CI: 108.57 to 109.40) in 2019. Regarding cardiomyopathy and myocarditis, the data evolved from 273.05 (95% CI: 272.62 to 273.47) in 1990 to 250.76 (95% CI: 250.42 to 251.09) in 2019. Concerning aortic aneurysm, the index transitioned from 104.91 (95% CI: 104.65 to 105.17) in 1990 to 91.14 (95% CI: 90.94 to 91.35) in 2019. Pertaining to endocarditis, the figures shifted from-4.50 (95% CI: −4.64 to-4.36) in 1990 to 16.00 (95% CI: 15.88 to 16.12) in 2019. As for rheumatic heart disease, the data transitioned from-345.95 (95% CI: −346.47 to-345.42) in 1990 to-204.34 (95% CI: −204.67 to-204.01) in 2019. Moreover, the relative concentration Index for overall CVD and each specific type also varied from 1990 to 2019. Conclusion There’s significant heterogeneity in transnational health inequality for ten specific CVDs. Countries with higher levels of societal development may bear a relatively higher CVD burden except for rheumatic heart disease, with the extent of inequality changing over time.